Penerapan Benchmarking dalam Meningkatkan Kinerja Institut Agama Islam di Indonesia - Asep Kurniawan (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2020)
Benchmarking encourages an institution to look deep into the process of similar competitors, and is proven to provide better results. But, this strategy is often forgotten. The purpose of this study is to uncover the application of benchmarking in improving performance at Islamic State Institute Sheikh Nurjati and Islamic Institute Bunga Bangsa, Cirebon, West Java. This research is a multi-case studi with qualitative approach. Data were collected by participant-observation, documentation-studi, and in-depth interviews. Analysis techniques were conducted through collecting data, reducing data, displaying data and concluding data. The results showed that benchmarking at Islamic State Institute Sheikh Nurjati and Islamic Institute Bunga Bangsa, Cirebon was sufficient to provide results in improving the performance of good institutions. Benchmarking plans were formulated through comprehensive planning and team building. Benchmarking implementation was formulated by selecting and adapting the results of benchmarking and taking into account the conditions of the institution. Benchmarking control in improving performance at both institutes is carried out through good communication between leaders, subordinates, and all education stakeholders.